1. First, you must find the constant of variation (k). The problem indicates that the base of each triangle varies inversely with the height. So, this can be represented as below:
 B=k/H
 B is the base of the triangle (B=10).
 H is the height of the triangle (H=6).
 k is the constant of variation.
 2. When you clear "k", you obtain:
 B=k/H
 k=BxH
 k=10x6
 k=60
 3. Now, you have:
 B=60/H
 4. You can give any value to "H" and you will obtain the base of the second triangle.
 5. If H=12, then:
 B=60/H
 B=60/12
 B=5
 6. Therefore, the possible base and height of a second triangle is:
 B=5
 H=12